Strengthening assessment and response to mental health needs for Aboriginal and Torres Strait Islander children and adolescents in primary care settings: study protocol for the Ngalaiya Boorai Gabara Budbut implementation project. Issue 9 (8th September 2022) - Reilly, Rachel; Azzopardi, Peter S; Brown, Alex; Fisher, Jane; Patton, George; Rickwood, Debra J; Yong, Choong-Siew; Pearson, Odette; Brown, Ngiare
Abstract : Introduction: Opportunities for improved mental health and wellbeing of Aboriginal and Torres Strait Islander children and young people lie in improving the capability of primary healthcare services to identify mental healthcare needs and respond in timely and appropriate ways. The development of culturally appropriate mental health assessment tools and clinical pathways have been identified as opportunities for strengthening workforce capacity in this area. The Ngalaiya Boorai Gabara Budbut implementation project seeks to pursue these opportunities by developing and validating a psychosocial assessment tool, understanding what services need to better care for your people and developing resources that address those needs. Methods and analysis: The project will be governed by a research governance group comprising Aboriginal service providers, young people, and researchers. It will be implemented in an urban health service in Canberra, and regional services in Moree, Wollongong, and the Illawarra regions of New South Wales Australia. The validation study will follow an argument-based approach, assessing cultural appropriateness and ease of use; test–retest validity; internal consistency, construct validity and the quality of decisions made based on the assessment. Following piloting with a small group of young people and their caregivers (n=10), participants (n=200) will be young people and/or their caregivers, attending one of the partner services. The needs assessment will involve an in-depth exploration of service via an online survey (n=60) and in-depth interviews with service providers (n=16) and young people (n=16). These activities will run concurrently. Service providers, researchers and the governance group will codesign resources that respond to the needs identified and pilot them through the participating services. Ethics and dissemination: The Aboriginal Health and Medical Research Council of NSW Human Research Ethics committee (#1769/21) has approved this project. Informed consent will be obtained from all participants and/or their caregivers (with assent from those aged <16 years) prior to participating in all aspects of the study. Research dissemination will occur through participating health services, academic journal articles and conference presentations.